Disentangling the drivers of understorey species richness in eutrophic forest patches. (21st November 2014) - Peppler‐Lisbach, Cord; Beyer, Linda; Menke, Nadine; Mentges, Andrea; Foster, Bryan
Abstract Questions What are the driving factors for the species richness of understorey herbs of isolated forest patches? How can the relative direct and indirect effects of patch area, site quality, habitat isolation and continuity be disentangled? What are the effects on different species groups? Location Eutrophic hardwood forest patches in northwestern Germany. The isolation of these patches results from extensive agricultural land use and prevailing poor soil conditions in the surrounding landscape. Thus, the patches are embedded within a matrix of both open habitats and species‐poor acidic forests. Methods We surveyed 76 eutrophic forest patches and recorded all understorey herb species. Several measured site variables were divided into soil and structural components, and into variables describing mean site conditions and site heterogeneity. Partial least squares structural equation modelling (PLS‐SEM) was employed to determine the direct and indirect effects of patch area, site heterogeneity, mean site conditions, isolation and habitat continuity on species richness of several species groups. Results The most important factor determining species richness was patch area, which showed the strongest direct effect on eutrophic forest specialist species. Richness of forest matrix species, which also occur in the surrounding forest areas, was not directly influenced by area. Soil heterogeneity as well as structural heterogeneity increased with area, but only soil heterogeneity was relevant for species richness. Soil heterogeneity was more important for forest species in general and stress tolerators than for generalist species, open habitat species, competitors and ruderals. Mean site conditions influenced species richness of generalists, open habitat species, competitors and nutrient‐demanding species. Isolation had a (negative) effect only on habitat specialists. Conclusions The relative effects of driving factors varied considerably between species groups. From our results for eutrophic forest specialists, we conclude that large and well‐connected habitat patches are especially important for the successful conservation of the unique and partly endangered flora of eutrophic hardwood forests.